PENERAPAN SISTEM ACTIVITY BASED COSTING SEBAGAI DASAR PENETAPAN TARIF LEMBAGA PENDIDIKAN PADA THE BRIDGE MANADO - Popang, Andika Saputra; Pontoh, Winston; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
Activity Based Costing system (ABC) is an accounting system that calculates cost based on activities in a company and charge the cost to the product based on cost driver. Therefore, ABC system removes cost distortion that occurs on conventional accounting cost system, and is able to produce a more accurate cost value. This research aims to determine the difference between ABC and conventional cost system in determining the cost of goods sold in an educational institution at PT. Anugerah Bina Bersama Abadi. The results shows that cost of goods sold using the ABC system when compared to the conventional accounting cost on the English and TOEFL Class are lower, with a difference of Rp.21.746,6 and Rp.159.001,15 respectively, while higher on the Community Class with a difference of Rp.153.969,74.Rp.153.969,74.Keywords: Activity based costing, cost of goods sold